SP0143 Ultrasound for Diagnosing Inflammatory versus Mechanical Midfoot Pain and Relevant Guided Interventions with Demonstration. (15th July 2016) - Siddle, H.
Abstract : The midfoot is a relatively unknown entity and difficult to examine clinically. Recent inflammatory arthritis studies have demonstrated that patients in disease remission may still have active disease in those residual joints not included in commonly used disease activity assessments. Osteoarthritis (OA) of the midfoot has previously been reported as being relatively uncommon (prevalence of 3.8%) however recent studies have highlighted that medial midfoot OA is more prevalent than previously described. Halstead et al (2015) reported changes most frequently in the cuneiform-second metatarsal joint (73%), followed by the naviculo-medial cuneiform joint (51%), the cuneiform-first metatarsal joint (46%) and the talo-navicular joint (24%), with patients indicating pain to the dorsal midfoot area. The midfoot is a complex structure and frequently undertreated. Differentiating between inflammatory and mechanical disease in the midfoot will enable the clinician to direct their treatment strategies more appropriately. Ultrasound imaging offers the clinician the opportunity to differentiate between joints that require treatment with mechanical interventions such as orthoses and footwear, and those that may also require local treatment of inflammatory disease which may include a guided steroid injection to improve the clinical outcome. Disclosure of Interest: None declared